RNA elongation by respiratory syncytial virus polymerase is calibrated by conserved region V. - Molly R Braun; Laure R Deflubé; Sarah L Noton; Michael E Mawhorter; Chadene Z Tremaglio; Rachel Fearns (PLoS Pathogens, 2017)
The large polymerase subunit (L) of non-segmented negative strand RNA viruses transcribes viral mRNAs and replicates the viral genome. Studies with VSV have shown that conserved region V (CRV) of the L protein is part of the capping domain. However, CRV folds over and protrudes into the polymerization domain, suggesting that it might also have a role in RNA synthesis. In this study, the role of respiratory syncytial virus (RSV) CRV was evaluated using single amino acid substitutions and a small molecule inhibitor called BI-D. Effects were analyzed using cell-based minigenome and in vitro biochemical assays. Several amino acid substitutions inhibited production of capped, full-length mRNA and instead resulted in accumulation of short transcripts of approximately 40 nucleotides in length, confirming that RSV CRV has a role in capping. In addition, all six variants tested were either partially or completely defective in RNA replication. This was due to an inability of the polymerase to efficiently elongate the RNA within the promoter region. BI-D also inhibited transcription and replication. In this case, polymerase elongation activity within the promoter region was enhanced, such that the small RNA transcribed from the promoter was not released and instead was elongated past the first gene start signal. This was accompanied by a decrease in mRNA initiation at the first gene start signal and accumulation of aberrant RNAs of varying length. Thus, in addition to its function in mRNA capping, conserved region V modulates the elongation properties of the polymerase to enable productive transcription and replication to occur.